Removal of zinc from simulated wastewater using chitosan coated coconut shell charcoal / Sanusi S. N. A ...[et al.] - Sanusi, S.N.A; Noh, N; Bakri, N.S; Mohd Redzuan, N.N; Muhamad Faizul Tan, F. A. T
An efficient adsorbent was prepared using coconut shell charcoal to remove zinc and the study was made. Modified coconut shell charcoal with coated of chitosan and/or oxidizing agent which is sulphuric acid are used as the adsorbent as the study was undertaken to produce a low cost yet effective biosorbent. The adsorption process was determined and the efficiency was evaluated by measuring the extent of adsorption of zinc in simulated wastewater. Each of the adsorbent was analyzed based on the percentage of removal efficiency, pH and adsorbent dosage. The result was characterized with inductively coupled plasma optical emission spectroscopy (ICP-OES). The maximum adsorption of Zinc (99.914%) was observed at 59.11 mg/L of ZnCl2 and adsorbent dose of 5 g for chitosan acid treated coconut shell charcoal (CACSC). It is beneficial that the use of coconut shell and chitosan to produce activated carbon potentially leads to the production of a highly effective adsorbent generated from less expensive raw materials that are from renewable resources.